Influence of ankle functional instability on the ankle electromyography during landing after volleyball blocking - Suda, E. Y.; Ferreira Amorim, C.; de Camargo Neves Sacco, I. (Journal of Electromyography and Kinesiology, 2009)
The purpose of this study was to describe, interpret and compare the EMG activation patterns of ankle muscles - tibialis anterior (TA), peroneus longus (PL) and gastrocnemius lateralis (GL) - in volleyball players with and without ankle functional instability (FI) during landing after the blocking movement. Twenty-one players with FI (IG) and 19 controls (CG) were studied. The cycle of movement analyzed was the time period between 200 ms before and 200 ms after the time of impact determined by ground reaction forces. The variables were analyzed for two different phases: pre-landing (200 ms before impact) and post-landing (200 ms after impact). The RMS values and the timing of onset activity were calculated for the three studied muscles, in both periods and for both groups. The co-activation index for TA and PL, TA and GL were also calculated. Individuals with FI presented a lower RMS value pre-landing for PL (CG = 43.0 ± 22.0; IG = 26.2 ± 8.4, p < 0.05) and higher RMS value post-landing (CG = 47.5 ± 13.3; IG = 55.8 ± 21.6, p < 0.10). Besides that, in control group PL and GL activated first and simultaneously, and TA presented a later activation, while in subjects with FI all the three muscles activated simultaneously. There were no significant differences between groups for co-activation index. Thus, the rate of contraction between agonist and antagonist muscles is similar for subjects with and without FI but the activation individually was different. Volleyball players with functional instability of the ankle showed altered patterns of the muscles that play an important role in the stabilization of the foot-ankle complex during the performance of the blocking movement, to the detriment of the ligament complex, and this fact could explain the usual complaints in these subjects.